Research types and innovation performance: the mediating effect of paper influence and patent novelty. Issue 8 (3rd August 2022) - Qiu, Shunli; Cao, Qinwei; Jiao, Meng; Liang, Sijing
ABSTRACT: In order to clarify which types of research is more conducive to improving innovation performance, we use the panel data of key universities in China from 2009 to 2017 for empirical research. The results show that basic research intensity is significantly positive correlated with innovation performance, while paper influence, patent novelty plus the interaction between paper influence and patent novelty are all playing a mediating role between basic research intensity and innovation performance. Furthermore, we use applied research intensity, experimental development intensity and provincial panel data for variables substitution and sample subdivision to carry out robustness test, clarifying the functional mechanism and the heterogeneity of boundary conditions between different types of research intensity and innovation performance. Relevant conclusions are of great theoretical and practical value for optimising the allocation of S&T resources and enriching the theoretical system of innovation research.